Synthesis of polymer coated Co0.5Zn0.5Fe2O4 nanoparticles and their enhanced anticancer activity against HepG2 cell line. (11th May 2018) - Ali, Z; Abbasi, R; Khan, A J; Arshad, J; Atif, M; Ahmad, N; Khalid, W
Abstract: Cobalt zinc ferrite nanoparticles with stoichiometry Co0.5 Zn0.5 Fe2 O4 (CZFN) were synthesized by sol-gel method with high colloidal stability having room temperature ferromagnetism. For biological applications, CZFN were transferred to aqueous phase by polymer coating with amphiphilic polymer, whereas fluorescent dye (ATTO-590) was used as model system for anti-cancer drug loaded polymer shell. The amount of functional molecule varied up to 25% of the anhydride rings, which provides greater affinity of drug loading in polymer shell. CZFN were characterized by x-ray diffraction, Fourier transformed infrared spectroscopy, UV–vis absorption spectroscopy, gel electrophoresis and vibrating sample magnetometer. The in vitro cytotoxicity of CZFN was examined against HepG2 which revealed that CZFN (IC50 :3.01 nM) strongly inhabits growth of the cells. Further the particles did not induce any significant hemolysis. Stimulatingly, this seems to be a noteworthy improvement towards the ability of surface functionalized multifunctional CZFN as carriers for drugs for anti-cancer therapy and their use as nanomedicine.